Native Habitats for Monarch Butterflies in South Florida - Rebecca G. Harvey; Patricia L. Howell; Carol Morgenstern; Frank J. Mazzotti (EDIS)
WEC266, a 5-page illustrated fact sheet by Rebecca G. Harvey, Patricia L. Howell, Carol Morgenstern, and Frank J. Mazzotti, describes the unique migration of the monarch butterfly, an “endangered natural phenomenon,” the monarch population in Florida, and the role of milkweeds and other host and nectar plants in appropriate monarch habitats for South Florida. Includes references (in HTML only). Published by the UF Department of Wildlife Ecology and Conservation, September 2009.